Arbuscular mycorrhiza suppresses microbial abundance, and particularly that of ammonia oxidizing bacteria, in agricultural soils - Sun, Daquan; Šmilauer, Petr; Pjevac, Petra; Rozmoš, Martin; Forczek, Sándor T.; Kotianová, Michala; Hršelová, Hana; Bukovská, Petra; Jansa, Jan (Frontiers in Microbiology, 2025)
Interactions between arbuscular mycorrhizal (AM) fungi and ammonia-oxidizing (AO) microorganisms, two important microbial guilds contributing to soil-plant mineral nutrient cycling, are complex, given the high variability of soil biological, physical, and chemical properties. In addition, AO microorganisms are generally slow growing and require ample time to establish. Their communities are thus difficult to reconstruct under laboratory conditions, for example after soil sterilization. Therefore, in this study, we investigated quantitative and compositional responses of indigenous microorganisms occurring in 50 different field soils (collected from grasslands and arable fields) to actively growing mycelium of the AM fungus Rhizophagus irregularis. To this end, we quantified the abundance of various microbial guilds including AO bacteria (AOB), AO archaea (AOA), and comammox Nitrospira in pot-incubated soils exposed or not to actively growing AM fungus. Across the variety of soils, we observed systematic suppression by the AM fungus of different microbial groups including bacteria, protists, and fungi. The strongest suppression was noted for AOB and comammox Nitrospira, whereas the abundance and community structure of AOA remained unaffected by the AM fungal activity. Mycorrhizal suppression of AOB abundance was accompanied by changes in AOB community structure and correlated with soil pH. Contrary to the expected competition between AM fungus and AO microorganisms for available ammonium (NH4+) in the soil solution, the presence of the actively growing AM fungus significantly increased soil NH4+ levels as compared to the non-mycorrhizal control, at least upon the final destructive harvest. Thus, the interaction between the AM fungi and AO microorganisms likely goes beyond the simple competition for the free ammonium ions and might involve microorganisms active in other pathways of soil nitrogen cycle (e.g., mineralization) or temporarily different trajectories of nutrient use in mycorrhizal vs. non-mycorrhizal systems. Alternatively, elusive biological nitrification inhibitors may have contributed to the observed effect, produced by the AM fungus or its host plant, and subsequently transported to the root-free soil via the AM fungal hyphae.